The anatomy and morphology of Taenitis Willd. ex Sprengel (Monilophytes) in Peninsular Malaysia - Haja Maideen,; Nurul Nadhirah,; Nur Aliah,; Nik Norhazrina, (Universiti Kebangsaan Malaysia, 2023)
The present study investigates the anatomical and morphological characteristics of four Taenitis species sampled from several localities in Peninsular Malaysia, namely Taenitis blechnoides, T. interrupta, T. dimorpha and Taenitis sp. The morphological and anatomical characters were observered with compound and dissecting microscopes, and sliding microtome. The species exhibited varying frond sizes (length and width) and positions of sori. Conversely, all the species showed common short creeping rhizomes with black hairy scales, scales at the base of stipes, U-shaped steles, simple trichome, sclerenchyma cells under the epidermis on stipes and rhizomes, polocytic stomata, and sinuous anticlinal walls. Morphologically, the frond form of Taenitis sp. is distinct from the other Taenitis. Thus, the species could be a new record for ferns in Peninsular Malaysia. However, molecular studies are required to confirm this.